USAHA GURU KEWIRAUSAHAAN DALAM MEMPERSIAPKAN SISWA UNTUK MENGHADAPI PERSAINGAN LAPANGAN KERJA DI SMK NEGERI 1 SINABANG - Arianto Fogus; TM Jamil; Zulfadhli Zulfadhli (Jurnal Ilmiah Mahasiswa Pendidikan Ekonomi, 2019)
The study entitled Entrepreneurship Teacher Efforts in Preparing Students to Face Job Competition in SMK Negeri 1 Sinabang is motivated by Indonesia today to be a member of the Asean Economic Community which requires prospective workers to have strong mentality, knowledge, and adequate skills. This situation is a demand for education, especially education in Vocational High Schools in preparing their students to be ready to compete to face job competition. This study aims to determine (1) the entrepreneurial teacher's business in preparing students to face job competition and (2) the supporting factors and inhibiting factors of entrepreneurial teacher's business in preparing students to face job competition. The data source of this research is entrepreneurship teacher at SMK Negeri 1 Sinabang. The approach used is qualitative and descriptive research type, with data collection techniques such as observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions. The results of entrepreneurial teacher's research efforts in preparing students to face competition in employment is by providing motivation and an illustration that at this time to find work is very difficult, besides the teacher also teaches students to entrepreneurship with the hope that later they can open their own jobs. Supporting factors and inhibiting factors for teachers' efforts in preparing students to face job competition include supporting factors, namely that the school continues to support and gives students the freedom to express creative ideas in entrepreneurship, and the inhibiting factors are things that have not been done before by students continue, constrained by funds in schools and galleries to display student work is still lacking, and the scope for developing student products is limited.